Renal response to frusemide in preterm infants with respiratory distress syndrome during the first three postnatal days. Issue 7 (July 1985) - Yeh, T F; Raval, D; John, E; Pildes, R S
Abstract : The renal effects of frusemide treatment in infants with respiratory distress syndrome shortly after birth and during the first three postnatal days were evaluated. Eighty five infants were randomly assigned to two groups. Forty two received three doses of intravenous frusemide (1 mg/kg) starting at age, mean (SD) 7.5 (4.1) hours and given at approximately 24 hour intervals. Forty three control infants were treated similarly but were not given frusemide. The groups were comparable in birthweight, gestational age, and Apgar score and in pulmonary status, blood gases, serum electrolytes, and postnatal age. Infants who received frusemide had significantly higher fractional excretion of sodium and chloride at 12 to 24, 24 to 48, and 48 to 72 hours, and higher calcium excretion at 24 to 48 and 48 to 72 hours after entry into the study than control infants. The study group had a significantly higher urine output and greater weight loss than the control group at 48 to 72 hours after entry into the study. There was no significant difference between groups in serum sodium, potassium, and calcium and in fractional excretion of potassium and the glomerular filtration rate. Infants with an Apgar score of more than 3 had higher urine output and had a better diuretic response to frusemide than those with a lower score. The results suggest that perinatal hypoxia may play an important role in renal function and in diuretic response to frusemide shortly after birth and early in the postnatal life of infants with respiratory distress syndrome.